HISTORY OF INTRAPLATE PACIFIC VOLCANISM FOR THE LAST 120 MILLION YEARS - Matveenkov V.V.; Sedov A.P.; Pristavakina E.I. (My University, 1998)
A large body of data was collected in this study and systematized in terms of the ages of intraplate volcanic activities in the Pacific Ocean. Analysis of the data revealed a dependence of the intensity of volcanism on the accretion rate of the oceanic plate. Several peaks of volcanic activity were identified in a period from the Cretaceous to the present time. Paleoreconstruction maps of the Pacific were prepared for the periods of increased volcanic activity using a technique developed at the Laboratory of Paleogeodynamics, Shirshov Institute of Oceanography. The maps suggest the conclusion that the localization of intraplate volcanoes was and is controlled mainly by stress dynamics in the oceanic lithosphere. Stresses were and are released in zones of structural weakness, e.g., in transform faults.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая